A contemporary view of occupational therapy in acute hospitals in metropolitan Western Australia - Britton, Lauren Heather (Curtin University, 2016)
Ongoing healthcare reforms within Australia continue to shape occupational therapy practice within acute hospitals. This thesis explores the practice challenges experienced by occupational therapists in the acute context and the responses they are making to their practice as a result in this setting. It discusses a need for occupational therapists to re-form their approach to acute care practice to ensure ongoing relevance to the health system where further innovations will influence future healthcare provision.